Parámetros genéticos de las características biométricas del fruto y semillas en Pachira aquatica Aubl. (2018)
Pachira aquatica is a tree whose fruits and seeds are used for human and animal nutrition in tropical regions. However, no research of its genetic variability have yet been reported to choose the best breeding method for the species. The objective of the study was to evaluate the genetic parameters of the biometric characteristics of the fruit and its seeds. The study was conducted at the Universidad de Córdoba, Colombia. Ten trees were selected and, of each, 10 fruits were randomly selected. Analysis of variance and estimation of genetic parameters were carried out for 15 characteristics of both organs. Significant differences were detected between trees for weight/fruit (FW), weight of husk/fruit (FHW), percentage of seeds/fruit (FSP), seed width (SW), seed thickness (ST), volume of a seed (S1V) and density of a seed (S1D). The greatest estimators of genetic variability were presented in ST, FSP, FHW and FW, where the genetic component represented more than 50% of the phenotypic variance. The highest heritability, both broad (h2A>76%) and narrow (h2E>30%), was for ST and FSP. The expected genetic gain, as a percentage of the general average, was less than 10% in 14 of the 15 characteristics studied, except for FHW (10.86%), therefore a modest genetic progress is expected for such characteristics. It is recommended to increase the local population genetic base and make genetic assays in several potential producing areas.